Tujuan dan Rancangan Program Diklat Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Tengah - Zahra Zahra; Abdul Gofur (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This article aims to provide an in-depth insight into appropriate training objectives, so as to improve the effectiveness of education and training programs and achieve the desired results. In the context of organizational strategy and training program design, training objectives play an important role. Clear and purposeful training objectives can help improve the effectiveness of training programs, motivate trainees, and provide indicators of success that can be evaluated. This study used a qualitative descriptive approach. The data collection methods used were observation, interview, and documentation. The results showed that clear and well-defined training objectives are essential in designing an effective training program. The research also emphasizes the importance of training objectives in the context of organizational strategy, where appropriate training objectives can help the organization achieve its goals and respond to existing needs. This article contributes to the understanding of the importance of training objectives in improving the effectiveness of education and training programs. The results of this study can serve as a basis for organizations, especially the Central Kalimantan Province Human Resources Development Agency, in designing more effective training programs and ensuring the achievement of organizational goals through human resource development.